Product development for pregnant consumers : reflections through favorite clothes (ModaPalavra e-periódico, 2016)
This paper shows results of a research aimed to understand the relationship between clothing and the pregnancy state of women in adulthood, as well as to investigate the importance of these sartorial relationships with the changes of the body. The data were generated via the testimony of eleven adult women in different gestational stages, so that the information has been treated through methods of qualitative analysis, in particular, the content analysis. It was used the Indicators of Consumption for Fashion-Clothing Products to collect via questionnaires and semi-structured interviews the sample participants‟ thoughts about their Favorite Clothes. The relationships found in this work suggest that the application of Favorite Clothing may be a successful tool for new product development dedicated to specific targets.
Keywords: pregnant women; clothing; bodily changes